Compatibility of Fuzi and Ginseng Significantly Increase the Exposure of Aconitines - Chen, Ze-Yan; Wei, Xu-Ya; Qiu, Zi-Dong; Huang, Yun; Tan, Ting; Feng, Yu-Lin; Guo, Juan; Cui, Guang-Hong; Huang, Lu-Qi; Lai, Chang-Jiang-Sheng (Frontiers in Pharmacology, 2022)
The herb-pair ginseng-Fuzi (the root of Aconitum carmichaelii) is the material basis of Shenfu prescriptions and is popular in traditional Chinese medicine for the treatment of heart failure, and even shock with severe-stage of COVID-19. A narrow therapeutic window of Fuzi may cause significant regional loss of property and life in clinics. Therefore, systemic elucidation of active components is crucial to improve the safety dose window of Shenfu oral prescriptions. A high performance liquid chromatography-mass spectrometry method was developed for quantification of 10 aconitines in SD rat plasma within 9 min. The limit of detection and the limit of quantification were below 0.032 ng/mL and 0.095 ng/mL, respectively. Furthermore, a systemic comparison with their pharmacokinetic characteristics after oral administration of a safe dosage of 2 g/Kg of Fuzi and ginseng-Fuzi decoction for 24 h was conducted. Eight representative diester, monoester, and non-ester aconitines and two new active components (i.e. songorine and indaconitine) were all adopted to the elucidate the differences of the pharmacokinetic parameters in vivo. The compatibility of Fuzi and gingseng could significantly increase the in vivo exposure of active components. The terminal elimination half-life and the area under the concentration-time curve of mesaconitine, benzoylaconitine, benzoylmesaconitine, benzoylhypaconitine, and songorine were all increased significantly. The hypaconitine, benzoylmesaconitine, and songorine were regarded as the main active components in vivo, which gave an effective clue for the development of new Shenfu oral prescriptions.